The europeanization of spatial planning processes in Portugal within the EU cohesion policy strategies (1989-2013) - Medeiros,Eduardo (2014)
Portugal is a young European democracy. However, it has been a member of the European Union (EU) for twenty seven years. During this time, it received more than 75 billion euros from the EU Cohesion Policy, in order to correct regional imbalances and to boost territorial development. As might be expected, the intervention strategies designed for these programming cycles had a profound influence from the European Commission (EC) guidelines and proposals. Hence, the goal of this article is to present a critical analysis of evolution of the EU Cohesion Policy strategic guidelines and the influence of the ESDP, the Territorial Agendas and the ESPON Programme in the design of these strategies, and its consequences in the Portuguese territorial development, during the last two decades.